Exploring EFL Students’ Perspectives: Integrating Mind Mapping as a Cognitive Tool in Academic Writing Class - Tupalessy, Pricilia; Matatula, Marles Yohannis; Lekatompessy, Felicia Miranda (TLEMC (Teaching and Learning English in Multicultural Contexts), 2024)
The purpose of the study is to find out the EFL students’ perspective on the use of mind mapping as a cognitive activity in an academic writing class in the English education study program at Pattimura University. This study took 3 students (1 male and 2 females) from an English education study program. The In-depth interview is the instrument of data collection with qualitative as the research method. The result shows that the EFL students’ perceptions toward mind mapping seemed to have positive responses toward their language learning with several benefits based on their experience during academic writing class, such as the writing of students was more well-structured, increased students writing grades in academic writing and the beneficial using mind mapping made them becomes motivated in writing something. However, in the process, there were several difficulties that some students had to face when using this strategy such as they were to determine the sub-points and doing the mind mapping took more time, energy, and thoughts, and they were confused about where to start making a mind map. The study suggests that using mind mapping in writing classes, with proper support and training, can help students improve their writing skills. Encouraging its use in other subjects and adapting teaching based on feedback can make mind mapping a valuable tool for better learning and academic success. Keywords: Mind Mapping, Cognitive Tool, Academic Writing